Maukah Anda Mengerjakan Tugas Yang Lebih Sulit? Melihat Pengaruh Jenis Umpan Balik Terhadap Performa Dalam Mengerjakan Tugas (Task Performance) - Prihandini, Grin Rayi (Universitas Islam Negeri Raden Intan Lampung, 2022)
Our performance in carrying out tasks can be different for each task. This is experienced by college students, where performance in completing assignments in certain courses can be different from other courses. In the process, students receive feedback from lecturers regarding their performance in completing the task, which is then expected to be a way of correcting mistakes and show an improved performance. Even so, previous studies have seen that effect of feedback on performance is still inconsistent. Feedback intervention theory shows that feedback on performance can be seen from a person's motivation to do tasks at a higher level of difficulty. This research is an experimental study with a randomized-blocked two group design (post-test only). This study replicate previous research. The aim of the study was to see the effect of the type of feedback (positive and negative) on performance as seen from the motivation to do task at a higher level of difficulty. The results of the analysis of the chi square test were significant χ2 (1, n = 60) = 8.864, p <0.05. This shows that there is a difference in the task performance between the group that receive positive feedback and the group that receive negative feedback. The results of the study are in line with previous research that there is an effect of the type of feedback on college students’ task performance. The implications of this research can be applied to the field of education in providing feedback to college students regarding their task performance.Keywords: feedback; task-performance; college students